Grammatical collocations in German textbooks Beste Freunde A1 and A2: Forms, types, and thematic meanings - Santoso, Iman; Sudarmaji, Sudarmaji; Mulyati, Retna Endah Sri (LITERA, 2025)
The mastery of Collocation would support the achievement of a good language proficiency. However, the existence of collocations  in German language Textbook is often not recognized by either learners or teachers. Therefore, a study was needed to map the presence of collocations in German textbooks for beginners. This was a descriptive qualitative study using a textbook analysis approach. The theoretical framework was based on Hausmann's work (1984) on Basic-Collocator Model. The German textbooks Beste Freunde A1 and A2, which contain naturally occurring collocations in their texts, dialogues, and exercises, served as the data source. The research instrument was human instrument. Data validity and reliability were obtained through repeated readings and focus group discussions. The results of the study showed that: (1) the total frequency of collocation occurrences was 1524, distributed evenly from Beste Freunde A1.1 to A2.2; (2) there were eight forms of collocations, with the most frequent form being the combination of a noun and a verb. Based on type, the most common type of collocation is lexical collocation; (3) semantically, the meanings of the collocations could be grouped into school and education, holidays and travel, and leisure and vacation. These books offer authentic input essential for developing native-level language proficiency.